Modeling & simulation of micro reactor with nitration of 2-methyl-4,6 dihydroxy-pyrimidine - Mandal, Alok Kumar; Pandey, Raj Kishore; Asthana, Nandan; Kulkarni, Amol; Kulkarni, Bhaskar Dattatraya (Science and Technology of Energetic Materials, 2011)
Nitration of 2-methyl-4,6-dihydroxypyrimidine (MDP) using concentrated sulfuric acid and nitric acid as nitrating mixture is a highly exothermic and hazardous reaction. Conducting such reaction in a batch reactor follow an unsteady state and its trajectory depends on various important parameters such as initial reactor temperature, initial composition of reaction mass, temperature of circulating coolant, etc. However, over all productivity, process control and safety of the batch process is highly restricted due to lower surface to volume ratio. In the present work, an effort has been made to over come the limitations of batch reactor by using the novel micro reactor device. Micro reactor is having extremely high surface to volume ratio, which has been explored to carry out nitration of MDP both numerically as well as experimentally and the results were compared with conventional batch reactor. The micro reaction system has been modeled using two dimensional (2-D) heat flow and mass transfer equations. The kinetic rate equation for nitration of MDP has evaluated experimentally by differential method which is used in modeling of the micro reactor. The numerical results from the 2-D model for conversion and temperature profile along the length and radius of micro reactor have been compared with corresponding results obtained from batch reactor. In order to validate the model, several experiments were conducted in micro reactor set-up with the variation of flow rate, residence time, concentration, temperature, etc. The experimental results from micro reactor revealed that nitration of MDP takes place even at much lower concentration and lower residence time with better control of temperature profile. Also, the reaction takes place in laminar region compared to turbulent region in corresponding batch reactor setup.
Keywords: 2-D modeling; 2-methyl-4; 6 dihydroxypyrimidine; Batch reactor; micro reactor

Microreactor-based continuous process for controlled synthesis of poly-methyl-methacrylate-methacrylic acid (PMMA) nanoparticles - Dobhal, Anurag; Kulkarni, Amol; Dandekar, Prajakta; Jain, Ratnesh (Journal of Materials Chemistry B, 2017)
We have developed a microreactor-based continuous process for synthesizing PMMA nanoparticles (NPs), based on the principle of nanoprecipitation. Our objective was to identify the critical parameters governing the size of nanoparticles, produced in microreactors, to enable reproducible synthesis of mono-disperse particles. Experiments were carried out in a microreactor, where parameters like flow rates of aqueous and organic phases, residence time and polymer concentrations were varied to examine their influence on particle size and homogeneity. The results from Dynamic Light Scattering confirmed that the particle size decreased with decreasing residence time, whereas when the aqueous to organic phase flow rate ratio was changed sequentially from 9 : 1, 4 : 1, 7 : 3, 3 : 2, to 1 : 1 (v/v), the particle size increased. Particles fabricated using a microreactor demonstrated a narrow and homogenous distribution, thus confirming their monodispersity. TEM, SEM and XRD were also performed for morphology analysis and phase identification of the particles. Further, paclitaxel encapsulated PMMA nanoparticles were prepared using the microreactor, demonstrating an increase in mean size of around 30 nm and a slightly higher polydispersity index compared to the blank nanoparticles. The drug encapsulation efficiency and drug release kinetics of these nanoparticles were comparable to those prepared in batch-experiments, thus establishing the suitability of the technology for preparing drug-loaded nanoparticles. Also, it was observed that at all the residence times (10 min to 10 s), about 80% of the polymer got transformed into nanoparticulate form, thus confirming the efficiency of the microreactor. In recent times, much work has been conducted to synthesize polymeric nanoparticles using different types of microreactors, but they lack detailed investigation of the effect of various parameters on the physiochemical properties of the resulting particles. Our investigation synthesizes PMMA NPs, using microreactor technology, for the very first time, to the best of our knowledge. Furthermore, we have performed a detailed analysis of the influence of various process parameters on the size and uniformity of the resulting nanoparticles. These critical parameters can serve as a useful tool to synthesize a myriad of nanoparticles of alternative polymers, using microreactor technology.

Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.